2011
DOI: 10.1007/s10646-011-0822-y
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxicity of Corexit 9500 in mallard ducks (Anas platyrhynchos)

Abstract: Embryotoxicity of the oil dispersant Corexit 9500 was examined using fertilized mallard duck eggs. Corexit 9500 was topically applied below the air cell to eggs in volumes ranging from 0 to 100 μL on day 3 of incubation. The highest incidence of mortality occurred at developmental stage 4, one day post-Corexit 9500 application. Hatching success was significantly decreased among eggs treated with ≥ 20 μL of Corexit 9500 as compared to controls (P ≤ 0.047). No egg treated with ≥ 40 μL successfully hatched. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
(17 reference statements)
0
15
1
Order By: Relevance
“…During the spill 7 million liters of Corexit 9500 and 9527 oil dispersant was applied, 4.1 million liters was applied to the surface while 2.9 million was applied sub-surface (National Commission on the BP Deepwater Horizon Oil Spill and Offshore Drilling, 2011). Multiple studies show low to moderate toxicity of Corexit oil dispersants, both as the dispersant alone and when mixed with crude oil (US EPA, 2011; Anderson et al, 2009; George-Ares and Clark, 2000; Goodrich et al, 1991; Wooten et al, 2012). The environmental impact of the application of oil dispersant at these unprecedented volumes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…During the spill 7 million liters of Corexit 9500 and 9527 oil dispersant was applied, 4.1 million liters was applied to the surface while 2.9 million was applied sub-surface (National Commission on the BP Deepwater Horizon Oil Spill and Offshore Drilling, 2011). Multiple studies show low to moderate toxicity of Corexit oil dispersants, both as the dispersant alone and when mixed with crude oil (US EPA, 2011; Anderson et al, 2009; George-Ares and Clark, 2000; Goodrich et al, 1991; Wooten et al, 2012). The environmental impact of the application of oil dispersant at these unprecedented volumes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Wooten et al . () reported exposure to Corexit 9500A significantly impaired development and reduced hatching success of fertilized mallard duck eggs. Studies in marine invertebrates and fish have shown significant toxicity of oil and Corexit alone and in combination.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wooten et al . () showed exposure to Corexit 9500A significantly impaired development and reduced hatching success of fertilized mallard duck eggs. Valuable information about the immunotoxicity of individual PAHs has been provided in a number of studies (Burchiel & Luster, ; Gao & Burchiel, ; van Grevenynghe et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been multiple studies in a variety of species focusing on the toxicity of Corexit and other dispersants (Almeda, Hyatt, & Buskey, 2014;Hemmer et al, 2011;Toyota, McNabb, Spyropoulos, Iguchi, & Kohno, 2017;Wooten, Finch, & Smith, 2012), studies on sublethal and long-term effects of Corexit have been limited.…”
Section: Endocrine Activity Of Corexit 9500mentioning
confidence: 99%